A review of the genus Triancyra Baltazar (Ichneumonidae: Rhyssinae) from Vietnam, with descriptions of three new species - Pham, Nhi Thi; Broad, Gavin R.; Zhu, Chao-Dong; Achterberg, Cornelis Van (Zootaxa, 2018)
The genus Triancyra Baltazar, 1961 and two species, viz. Triancyra aurea Wang & Hu, 1992 and Triancyra graptothoracalis Wang & Huang, 1992, are reported for the first time from Vietnam. In addition, three species are described as new: Triancyra acuta sp. nov., and Triancyra mystaxa sp. nov. from Dak Lak Province in Central Highlands, and Triancyra cucphuongensis sp. nov. from Ninh Binh Province in northern Vietnam. A key for all five Vietnamese Triancyra is also compiled.